ICDS: is it reaching the all child beneficiaries? - Kumar, N. Pragathi; Ramchandra, Tagaram (International Journal Of Community Medicine And Public Health, 2019)
Background: The beneficiaries under the scheme are children in the age group of 0-6 years, pregnant women and lactating mothers, women in the age group of 15-44 years and adolescent girls in selected blocks. Irrespective of caste, religion, socioeconomic status all beneficiaries are eligible for availing of services under the Integrated Child Development Services (ICDS) scheme. BPL is not a criterion for registration of beneficiaries under ICDS2. Present study is to recognize whether all categories of people are utilizing the services or not irrespective of economic status, religion etc. Methods: Descriptive observational study done for period of one year, sampling done by multi stage (random) method. Study conducted in ICDS centers in the field practicing area of Kakatiya medical college Warangal, Telangana, India. 622 children from 31 anganwadi centres of 0 to 6 year age were included. Results: Majority (71.7%) were belongs to ‘0 to 3’ years of age group, male (50%) and female (50%) were equally in distribution. majority (78.3%) were Hindus. Majority parents (father-84.9, mother 84.2) were literates and mothers were unemployed/housewives, fathers were skilled workers (28%) followed by farmers (22%). Majority were (35.4%) belonged to middle, followed by lower middle (30.2%) level of socio economic status. Conclusions: There were less number of 3 to 6 years age category population in the study, means that age group is not getting covered properly by ICDS. Two extremes (higher and lower categories) of education, occupation, socio economic status parents were not properly utilising the ICDS services for their children.